DHA Supplement in Pregnant Women Life's Flow: Measure Before You Bestow - Sharma, Ritika; Thakur, Shubham (Current Nutrition & Food Science, 2025)
Docosahexaenoic Acid (DHA) supplementation is regarded as safe and beneficial to maternal health before, during, and after pregnancy. DHA is indeed an important fatty acid, and its requirement is elevated during pregnancy due to fetal brain and eye development requirements. Despite its established importance, there is no established Recommended Dietary Allowance (RDA) for DHA, unlike other essential nutrients. The other gap in the estimated average minimum required intake is due to individual differences in the needs of DHA among individuals. This depends on an individual’s diet, metabolism, and genetic effects. Although there are guides on the minimum daily intake, measurement using blood tests still remains the best way to determine an individual's needs. Therefore, patients should first consider monitoring their DHA concentration and then adjust supplementation according to personal requirements. Among the existing choices of DHA supplementations, traditional soft-gel capsules present some drawbacks viz lower stability, lower bioavailability, and organoleptic problems such as a fishy aftertaste. The emulsion-based DHA formulations, on the other hand, offer a better alternative with higher stability, better bioavailability, and a favorable taste profile. Therefore, the editorial highlights the need for tailored approaches such as estimating the baseline reference range in individuals’ blood and then supplementing the individual with DHA using novel delivery systems, such as emulsions. These tailored approaches will further enhance maternal and fetal health.
Keywords: preterm birth